The role of computed tomography in intra-axial posterior fossa tumors - Ali I. Sheaa; Mohammed Al-Hili; Ali K. Al-Shalchy (مجلة كلية الطب, 2015)
Background: CT (computed tomography) is one of the first noninvasive imaging techniques in diagnosis of intra-axial posterior fossa tumors because it can accurately demonstrate, localize and characterize brain tumors, and can provide important information about the anatomic location, size, shape of the lesions and their mass effect on adjacent structures. Objectives: To evaluate multi detectors CT characteristics of intra axial posterior fossa tumors and correlation of the CT characteristics of intra- axial posterior fossa tumors with the histopathological findings. Patients & Methods: This is a cross sectional study including 26 patients with intra-axial posterior fossa tumors,15 males &11 females ,three cases were excluded from the study because no definite histological diagnosis was done so the final included number was 23 cases .The cases were referred from the Department of Neurosurgery in Ghazi Al-Hariri specialized surgical hospital in Medical city complex at the period between January 2012 to January 2013. Results: The most common intra- axial posterior fossa tumors were astrocytoma, and medulloblastoma (26.1%) for both equally. These tumors are more common in pediatric age group (60.9%) than adult (39.1%). Medulloblastoma was the most common childhood tumors. Hemangioblastoma and metastasis were the most common adulthood tumors. The gender distribution of the total number of patients showed male predominance by a factor 1.5, (60.9%) were males, and (39.1%) were females. CT scan was sensitive in detection of tumors but it was not specific to give the definite histopathalogical tumors type. Conclusion: Medulloblastoma and astrocytoma were the most common intra axial posterior fossa tumos. The gender distribution showed male predominance. CT scan was sensitive in detection of tumors but it was not specific to give the definite histopathalogical tumors type. The confidence interval of CT in diagnosis of histopathlogical types is 65.2 % but it is still useful in the detection, localization and characterization of tumors.